Efficacy and safety of thromboprophylaxis with low-molecular-weight heparin or rivaroxaban in hip and knee replacement surgery - Beyer-Westendorf, Jan; Lützner, Jörg; Donath, Lars; Tittl, Luise; Knoth, Holger; Radke, Oliver C.; Kuhlisch, Eberhard; Stange, Thoralf; Hartmann, Albrecht; Günther, Klaus-Peter; Weiss, Norbert; Werth, Sebastian (Thrombosis and Haemostasis, 2013)
Prospective trials have shown that rivaroxaban thromboprophylaxis is superior over low-molecular-weight heparin (LMWH) in patients undergoing hip and knee replacement surgery. However, patients treated under trial conditions are different from unselected routine patients, which may affect efficacy and safety of thromboprophylaxis. The objective was to evaluate the efficacy and safety of rivaroxaban or LMWH thromboprophylaxis in unselected patients undergoing hip and knee replacement surgery in daily care. In a monocentric, retrospective cohort study in 5,061 consecutive patients undergoing hip and knee replacement surgery a comparison of LMWH (hospital standard in 2006–2007) and rivaroxaban (since 2009) was made with regard to rates of symptomatic VTE, bleeding and surgical complications and length of hospital stay. Rates of symptomatic VTE were 4.1 % (LMWH) and 2.1 % (rivaroxaban; p=0.005) with rates for distal DVT 2.5 vs. 1.1 % (p<0.001). Rates of major VTE were numerically higher with LMWH (1.7 vs. 1.1%, not statistically significant). Rates of major bleeding (overt bleeding leading to surgical revision or death, occurring in a critical site, or transfusion of at least two units of packed red blood cells) were statistically lower with rivaroxaban (2.9 vs. 7.0%; p<0.001). Rivaroxaban patients had fewer surgical complications (1.1 vs. 3.7%; p<0.001) and a shorter length of hospitalisation (8.3 days; 95% CI 8.1– 8.5 vs. 11.1 days; 10.7– 11.5; p< 0.001). We conclude that rivaroxaban thromboprophylaxis is more effective than LMWH in unselected patients undergoing hip and knee replacement surgery in daily care and that switching from LMWH to rivaroxaban could be beneficial. Prospective comparisons are warranted to confirm our findings.
Keywords: Low-molecular-weight heparin; major orthopaedic surgery; rivaroxaban; venous thromboembolism; VTE prophylaxis